Maternal Factors Affecting Birth Weight of New Born Babies Born in Combined Military Hospital Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Low birth weight (LBW) is one of the pernicious outcomes of pregnancy. To recognize the factors contributing to LBW is therefore of vital significance. But due attention had not been paid to address the issue. This study was carried out to candle the light on maternal demographic and health services factors on birth weight of a newborn baby.Objective: To depict the pattern of birth weight of newborn babies born at CMH Dhaka and to ascertain selected demographic (age, height) pattern and utilization of health service factors of the mothers.Materials and Methods: This cross-sectional study was conducted at Combined Military Hospital (CMH) Dhaka from September to December 2011 among 110 respondents. Data were collected by interview using a semi-structured questionnaire and were checked, edited, coded, categorized, cleaned and analyzed by using SPSS version 16.Results: Mothers’ age ranged from 19 to 36 years. Highest 43.6% of mothers belonged to the 20-25 years age group. Teenage mothers were 15.5%. Mothers above 25 years of age gave birth to higher percentage of average weight babies (88.9%) and teenaged (